Surface and subsurface geology of the Hontomín structure, Western Pyrenees - Eloi Carola; Eduard Roca; Anna Quintà; Josep Anton Muñoz (Journal of Maps)
A detailed geological study was conducted in the Hontomín area in the western Pyrenees, Northern Spain, focusing on structural characterization by integrating available subsurface data with a newly developed surface geological map. It reveals a relatively simple surface structure, with the Upper Cretaceous generally dipping gently eastward, except at the southern margin, where they are deformed into tight E-W-trending folds. In contrast, the unconformable Cenozoic layers dip only a few degrees southward. However, seismic data interpretation reveals a much more complex subsurface structure. It is dominated by a broad dome, cored by Upper Triassic salt, which has significantly influenced the overlying stratigraphy and structure. Above the salt, the Jurassic and Lower Cretaceous units exhibit moderate folding, a deformation style that is not apparent at the surface. The deep structure is controlled by a major E-W trending thrust fault, which is not clearly expressed at surface except through small-scale, tight folds aligned in the same direction. This study highlights the importance of integrating surface mapping with geophysical data, both for accurately interpreting subsurface geology when planning for CO₂ injection operations.